A Test Strategy for Discriminating between Autocorrelation and Misspecification in Regression Analysis: Reply - Thursby, Jerry G. (The Review of Economics and Statistics, 1985)
Jerry G. Thursby, A Test Strategy for Discriminating between Autocorrelation and Misspecification in Regression Analysis: Reply, The Review of Economics and Statistics, Vol. 67, No. 1 (Feb., 1985), pp. 177-178